STRATEGI PELAYANAN BANK KONVENSIONAL DAN SYARIAH: PRIORITAS PELAYANAN FISIK DAN EMPATI - RONI ANDESPA (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2016)
The research theme is the financial and banking institutions.  The study was conducted in West Sumatra. The object of the research is 250 sharia banks and 250 conventional banks research objectives are: (1) To see if there is a difference in perception based on the background of customers on variable tangible and empathy, (2) To see the relationship between the characteristics of the customer with variable tangible and empathy. The variables studied were: (1) Tangible, (2) Empathy, (3) Characteristics of respondents. The study is quantitative. Analysis of the data using (1) Cross Tabulation, (2) Pearson Chi-Square Test. Results of the study are: In the conventional banks (1) Between the tangible variables with the characteristics of customers no significant relationship. (2) There is a significant relationship between the variables of empathy with the educational of customers. Sharia bank (1) The existence of a significant relationship between the variables tangible with the age of the customer. (2) There is a significant relationship between the variables of empathy with the gender of customer.